Pengungkapan Emisi Karbon dan Kinerja Perusahaan - Andrew Giovano Hartono; Monika Palupi Murniati (Universitas Katolik Soegijapranata Semarang, 2026)
The concern of customers, suppliers, investors, and other stakeholders for environmental management is starting to become a consideration in decision-making. Stakeholder demands for sustainability require companies to manage their environmental impacts to maintain their financial performance. This study aims to present empirical evidence on the role of energy intensity, carbon intensity, and carbon emission disclosure as important contributors that can influence the financial performance of companies listed in five ESG indices on the Indonesia Stock Exchange (IDX) during 2020-2024. The study sample consists of companies listed in five ESG (Environmental, Social, and Governance) indices that are highly sensitive to environmental issues. The results show that stakeholders appreciate companies that are able to demonstrate tangible environmental impacts, such as reduced energy consumption and carbon savings. For companies, these findings demonstrate the importance of energy and carbon management as part of cost-efficiency strategies and environmental risk management. For investors, these indicators can be considered in assessing investment feasibility.